Pengaruh Rasio Keuangan terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di BEI pada Tahun 2021-2014 - Alia, Wahyu Rahma; Handriani, Eka; Suryatama, Fajar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study contains financial ratios that can affect a company's stock price. In this study, the ratios used are ROA, ROE, EPS, CR, and DER, which can potentially affect stock prices. This study is expected to help investors who want to invest in banking companies listed on the Indonesian Stock Exchange. The purpose of this study is to examine the effect of return on assets (ROA), return on equity (ROE), earnings per share (EPS), current ratio (CR), and debt to equity ratio (DER) on stock prices of banking companies listed on the Indonesian Stock Exchange in the period 2021–2024. In addition, this study is expected to provide empirical contributions to the development of literature in the field of investment and banking finance in Indonesia. The method used in this study is the panel data regression method, which is considered more appropriate in analyzing the relationship between financial variables across companies and across time compared to conventional linear regression methods. From several financial ratios tested, there are research results that some have an effect on stock prices. The coefficient of determination indicates that the independent variables, consisting of ROA, ROE, EPS, CR, and DER, are able to explain 89.6759% of stock prices in Indonesian banking companies, while the remaining 0.103241% is explained by other variables not included in this research model.